Vitamin D Deficiency and Maternal Diseases as Risk Factors for the Development of Macrosomia in Newborns - Nazym Ailbayeva; Aliya Alimbayeva; Oxana Yurkovskaya; Raida Faizova; Sayat Tanatarov; Gulnara Taiorazova; Aizhan Abylgazinova; Andrey Orekhov; Ulzhan Jamedinova; Lyudmila Pivina (MDPI AG, 2024)
Background: The aim is to assess the association between the level of vitamin D, maternal diseases, and macrosomia in newborns. Methods: This study included 258 full-term newborns (86 newborns with macrosomia; and 172 newborns with normal weight). Enzyme immunoassays for the determination of vitamin D were performed. Results: Newborns with macrosomia were statistically significantly more likely to have severe vitamin D deficiency compared with control (13.5 ± 6.7 ng/mL vs. 21.3 ± 12.1 ng/mL; p < 0.05). In the main group, severe deficiency was found in 40.7% of newborns, in the control group this rate was 5.8% (χ2 = 71,788, df = 3, p < 0.001). Multiple regression analysis shows that statistically significant risk factors for the development of macrosomia were vitamin D deficiency in the cord blood (OR = 2.29), maternal age over 36 years old (OR = 19.54), and hypothyroidism (OR = 9.35). Conclusion: the results of our study demonstrate relationship between macrosomia in newborns and vitamin D deficiency in the cord blood, maternal overweight and obesity, maternal age and thyroid disease.